2022
DOI: 10.3390/ani12050612
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Red Corn Rich in Anthocyanins on Productive Traits, Blood Metabolic Profile, and Antioxidative Status of Fattening Lambs

Abstract: In this study, we aimed to evaluate the effects of different proportions of red corn rich in anthocyanins on the diet of fattening lambs considering their productive traits, blood metabolic profile, and antioxidative status. The research was carried out with 30 Merinolandschaf lambs, 90 days old and weaned. The feed mixture for lambs (n = 10) of the control group contained yellow corn, while in the feed mixture of experimental group I (n = 10), yellow corn was replaced with red corn at 50% (RC50), and in exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…In this work, we investigated a novel type of corn with cobs rich in anthocyanin as roughage in feedlot lamb diets in comparison to regular corn cobs and commonly used grass hay for comparison. In accordance with the literature ( Prommachart et al, 2021b ; Antunović et al, 2022 ; Tian et al, 2022 ), there was no effect of dietary anthocyanin on lamb DMI and growth performance. Prommachart et al (2021b) also found no differences in DMI when black rice and purple corn-extracted residue were tested in the diets of male dairy cattle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this work, we investigated a novel type of corn with cobs rich in anthocyanin as roughage in feedlot lamb diets in comparison to regular corn cobs and commonly used grass hay for comparison. In accordance with the literature ( Prommachart et al, 2021b ; Antunović et al, 2022 ; Tian et al, 2022 ), there was no effect of dietary anthocyanin on lamb DMI and growth performance. Prommachart et al (2021b) also found no differences in DMI when black rice and purple corn-extracted residue were tested in the diets of male dairy cattle.…”
Section: Discussionsupporting
confidence: 91%
“… Prommachart et al (2021b) also found no differences in DMI when black rice and purple corn-extracted residue were tested in the diets of male dairy cattle. Antunović et al (2022) observed no influence of red corn rich in anthocyanins in lamb diets on final BW, ADG, and DMI. Tian et al (2022) did not find the effects of feeding goats purple corn anthocyanin on DMI, ADG, or G:F.…”
Section: Discussionmentioning
confidence: 65%
“…Further intake is estimated to be inversely related to forage fiber content, since the slower digesting component increases in proportion to the digestive system volume [ 21 , 36 , 37 ]. Our findings are similar to those of [ 38 , 39 ], which showed that red maize high in anthocyanins can boost lamb productivity. As a result, polyphenol-enriched feeds, such as anthocyanins, are increasingly utilized as supplements added to solid feed after weaning, potentially leading to decreased oxidative stress and an enhanced immunological response, health status, and meat quality in lambs [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…In lambs, the highest mortality and metabolic disorders occur during the first few days or weeks of life, mainly due to inadequate maternal feeding and poorly developed digestive systems of young lambs [ 53 ]. This problem, if not noticed and properly treated in time (late gestation; early lactation), can cause significant economic problems due to impaired productivity or mortality [ 54 ].…”
Section: Discussionmentioning
confidence: 99%